SIMULATION OF THE BEHAVIOR OF A MULTICOMPONENT MIXTURE IN SIMPLE BATCH DISTILLATION - Otiniano C., M. (2012)
We have developed a mathematical model for simulating the behavior of multicomponent mixtures on the single batch distillation using Rayleigh equation which can observe the behavior of components in the distillate and residue.